Evaluating the Knowledge, Attitude and Performance of Kermanshah Citizens about the Effects of Using Detergents and Abstergents on Hygienic, Environmental and Safety - Seyyed Alireza Mousavi; Maryam khashij; Sara Hamzeh (Iranian Journal of Health, Safety and Environment, 2017)
The published statistics show the increasing consumption of detergents and abstergents in recent decades. According to high utilization of these substances and their adverse consequences, the purpose of this study is evaluating the knowledge, attitude and performance of Kermanshah citizens about the hygienic, environmental and safety effects of using detergents and abstergents. This study is analytical and descriptive and the sample size was 386 persons from Kermanshah citizens in 2015. The methodology of this study is based on a self - made questionnaire and the Cronbach's alpha coefficient was 0.7. The SPSS - 20 was used for analyzing the data. 42.44% of them have high knowledge and 49% - 9% of them have respectively average and poor knowledge. 81.75% of participants have a positive attitude and 18.25% of them have negative one. Also 61.5% of participants have a proper performance and 38.5% of them don't have a proper performance. There was a positive and significant relation between knowledge based on attitude (r=0.03) and performance (r=0.2). And also it was found that there is a direct correlation between attitude and performance (r=0.04). Since 38.5% of participants had poor performance and this is not satisfactory, it is necessary to instruct and inform people continuously about using detergents and abstergents correctly for better and more efficient performance.